Development of HPLC-MS/MS method for simultaneus quantification of veterinary antibiotics and hormones in soil and biosolids - Ho, Yu Bin (2012)
Repeated applications of animal manure as fertilizer are normal agricultural practices that may release veterinary antibiotics and hormone into the environment from treated animals. The occurrence of veterinary antibiotics and hormone residues in the environment is of concern because of the development of antibiotic-resistant bacteria and its ecotoxicological behavior to plants and animals. To date, the occurrence of veterinary antibiotics and hormone in the Malaysian agricultural field has never been reported. The lack of data could be attributed to the absence of universal method for the analysis of veterinary pharmaceutical residues in complex solid environmental matrices. Therefore, a reliable, simple, fast and cost-effective method was developed in order to quantify nine antibiotics (doxycycline, enrofloxacin, erythromycin, flume quine, norfloxacin, sulfadiazine, tilmicosin, trimethoprim, tylosin) and one hormone (progesterone) in soil, broiler manure and manure compost. Generally, this method has shorter time of analysis, lower cost of solid phase extraction (SPE), better recoveries, lower method detection limit (MDL) and method quantification limit (MQL) values as compared to USEPA Method 1694, Kim and Carlson (2007) and Blackwell et aI, (2004). The current method was compared to the USEPA Method 1694where the method has the closest target analytes and sample matrices. The time of extraction has reduced from >125 mins to >63mins, the time of liquid chromatography analysis has reduced from 61 mins to 25 min and the cost of SPE cartridge has reduced from RM70.00 to RM10.30 per sample when compared to the USEPA Method 1694. The developed method was based on ultrasonic extraction with MeOH:ACN:EDTA:McIlvaine buffer (PH 4) (30:20:25:25),SPE using HLB (3ccj 60mg) cartridge, followed by instrumental analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS) with 25 mins total run time. The developed method was validated and tested on soil, broiler manure and manure compost samples and showed that the method is able to simultaneously detect and quantify the target analytes with good selectivity and sensitivity. The overall method performance was good for the majority of the analytes, with recoveries greater than 80%for most of the analytes in each type of sample matrix. MDL and MQL were achieved at as low as 0.5 and 2 ~g/kg dry weight (DW) for trimethoprim. Tilmicosin was first time reported in environmental matrices. The developed method was then applied on broiler manure samples and its relative manure amended agricultural soil samples collected in Selangor, Negeri Sembilan and Melaka to identify and quantify veterinary antibiotic and hormone residues in the environment. The broiler manure samples were found to be contaminated with at least seven target analytes, which are doxycyline, enrofloxacin, flumequine, norfloxacin, trimethoprim, tylosin and progesterone. The maximum concentration of antibiotic detected in broiler manure was 78516.1 flg/kg DW for doxycycline. For manure amended agricultural soil samples, doxycycline, enrofloxacin, flumequine and trimethoprim residues were detected in every soil samples. The maximum concentration of antibiotic detected in soil was 1331.4 flg/kg DW for flumequine. The results showed that the method can potentially be adopted for the analysis of veterinary antibiotic and hormone wastes in solid environmental matrices.